Crash analysis and evaluation of vehicular impacts on W-beam guardrails placed behind curbs using finite element simulations. (December 2017) - Gutowski, Matthew; Palta, Emre; Fang, Howie
Highlights: Developed FE models of single-faced W-beam guardrails installed behind curbs. Performed nonlinear FE simulations of vehicles impacting roadside curb-guardrails. Evaluated the effects of a curb on the performance of W-beam guardrails at different placement heights. Abstract: Roadway design, including the use of traffic barriers, is a critical aspect in transportation safety and is used to reduce the severity and frequency of automotive accidents. All barriers used on U.S. highways are designed according to the American Association of State Highway and Transportation Officials (AASHTO) Roadside Design Guide and are tested to ensure they satisfy the safety criteria specified by Manual for Assessing Safety Hardware (MASH). While curbs main functions are to separate the road from roadside, control vehicle rights-of-way, and channel water runoff; their use is discouraged by AASHTO from being installed on high-speed roadways due to the disruptive behavior caused when vehicles strike them. The destructive nature of vehicular crashes imposes significant challenges to barrier design using full-scale physical testing; numerical simulations thus become a viable option to support guardrail design improvements and performance evaluation. In this study, validated vehicle and W-beam guardrail models installed behind AASHTO Type B curbs were used to perform full-scale simulations of vehicle-curb-guardrail impacts. Seven single-faced W-beam guardrails, with placement heights of 27, 29, and 31 inches (0.69, 0.74, and 0.79 m), placed behind curbs at zero, six, and twelve foot offsets were impacted at 44 mph (70 km/h) and two impact angles (25° and 15°) by a 1996 Dodge Neon and a 2006 Ford F250. The guardrail's performance was evaluated by analyzing the maximum guardrail deflection and vehicular responses based on post-impact exit trajectory utilizing the MASH exit box criterion, rotational angles, and transverse and longitudinal displacements and velocities.